Management of severe tetanus in Afghanistan: lessons from the field - Spagnolello, Ornella; Aryan, Ahmad K; Ahmadzai, Muhebullah; Dost, Arezo; Boosti, Abdul G; Ceccarelli, Giancarlo; Portella, Gina; Baiardo Redaelli, Martina (The Journal of Infection in Developing Countries, 2024)
Introduction: Tetanus is a rather rare disease in the Western countries thanks to widespread vaccination programs and the availability of prophylactics for patients with tetanus-prone injuries. The few cases that do occur are promptly managed in intensive care units (ICUs). However, tetanus is not so rare in developing countries, where access to a suitable level of care is limited. An unstable political situation can be a significant factor influencing patient outcomes. Case report: A ten-year-old boy presented at the EMERGENCY hospital in Lashkar-Gah (southern Afghanistan) with generalized tetanus after falling off his bicycle. In response to his rapidly deteriorating general conditions – respiratory failure and hemodynamic instability – the patient was urgently transferred by ambulance to the ICU at the EMERGENCY hospital in Kabul (northern Afghanistan). The patient was placed on mechanical ventilation while receiving intravenous sedation and pharmacologic paralysis for almost four weeks. A prolonged infusion of a high dose of magnesium sulphate and labetalol was also given to counteract autonomic dysfunction. Multiple complications related to the long stay in the ICU were observed and promptly addressed. During this period, several mass casualties took place in Kabul, which stretched the hospital’s surge capacity. The patient was discharged and accompanied back to Lashkar-Gah three months after his admission to the hospital. Conclusion: This case report shows some of the many difficulties that arise when managing a patient with severe tetanus in a war zone where resources are limited.